Pengembangan Modul Materi Geometri Kelas IV Berbasis Masalah Berorientasi pada Penalaran Matematis Siswa - Sundari, Indah; Fuadiah, Nyiayu Fahriza; Fakhrudin, Ali (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
The research of this development aims to produce an ivy-based geomteri matter module based onproblems ordeals on valid, practical, and effective student mathematical reasoning. The kind ofresearch that is done is research and development (r&d) refers to the borg & gall model. Based onthe results of the test, it is obtained that (1) validation of the module in a very valid category (2) practical, judging by the observations of the module's alignment are in the category fully executed, and (3) effective, judging by the student's study tests being scored 85% absolutely and the student's mathematical reasoning has reached the minimum minimum criteria. So it can be concluded that the developed modules have met valid criteria, practicality, and effectiveness.